Photo-stimulated leaving group isomerization of acyl donor esters in protease-catalyzed hydrolysis reactions. Issue 6 (2nd November 2018) - Elsner, Christian; Lohan, Marcus; Griebel, Jan; Decker, Ulrich
Abstract: Hydrolysis studies of photo-switchable N -maleyl-amino acid-(4-phenylazophenyl) esters of Ala, Gly, Met, Phe, and Pro were performed using the proteases trypsin and chymotrypsin. It has been found out that the cis -isomers were hydrolyzed faster than the trans -isomers. In dependence of the amino acid in the P1 position the velocity graduation is Phe > Met > Ala > Gly > Pro for trypsin and Phe ≫ Met > Ala > Gly > Pro for chymotrypsin for both isomers.